Transcriptomic analysis reveals vector attraction to potato virus Y is mediated through temporal regulation of TERPENE SYNTHASE 1 (TPS1) - Chad T. Nihranz; Prakriti Garg; Junha Shin; Madeleine Dumas; Sunnie Grace McCalla; Sushmita Roy; Clare L. Casteel (Plant Stress)
Viruses alter plant traits over time, which can further influence interactions between plants and insect vectors that transmit those viruses. However, the signaling pathways and regulators that control these temporal responses remain largely unknown. In this study, we used insect performance and preference bioassays, RNA-seq, and genetic tools to identify underlying mechanisms mediating temporal variation in plant-virus-vector interactions. We show that settlement and fecundity of the aphid vector, Myzus persicae, is increased on potato virus Y (PVY)-infected Nicotiana benthamiana plants two weeks post inoculation but not after six weeks. RNA-seq analysis revealed that transcripts related to plant defense and amino acid biosynthesis are upregulated in response to PVY infection and down regulated in response to aphid herbivory, and these patterns changed over time. Based on this analysis we identified a sesquiterpene synthase gene, terpene synthase 1 (NbTPS1), that is upregulated early in PVY infection, but not later in infection. Using virus-induced gene silencing and transient overexpression in N. benthamiana, we demonstrate that PVY induction of NbTPS1 is required for increased aphid attraction to PVY-infected plants in the early stages of infection. These findings reveal that PVY temporally modulates transcriptional pathways associated with plant defense responses and volatile organic compounds that influence the behavior of aphid vectors.